2019
DOI: 10.15763/issn.2642-2387.2019.5.1.33-59
|View full text |Cite
|
Sign up to set email alerts
|

Students Perspectives on Holistic Mentoring Practices in STEM Fields

Abstract: This critical multi-site case study examined the holistic mentoring practices provided by faculty to Students of Color in STEM fields at a predominantly White institution and a historically Black institution.  We employed Bourdieu’s social reproduction theory to examine the ways in which social capital developed through faculty-student mentoring relationships led to the accumulation of cultural capital valued in STEM fields and higher education more broadly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Rather, the profession needs to invest time and resources in training the professionals most responsible for mentoring on how to best do it. Luedke, McCoy, Winkle‐Wagner, & Lee‐Johnson (2019) argued that graduate program faculty must be trained in culturally sensitive advising in order to make significant change. This could, they argued, lead to “disrupting processes that have historically perpetuated inequality in education experiences” (p. 54).…”
Section: Recruitment Questions Results and Implicationsmentioning
confidence: 99%
“…Rather, the profession needs to invest time and resources in training the professionals most responsible for mentoring on how to best do it. Luedke, McCoy, Winkle‐Wagner, & Lee‐Johnson (2019) argued that graduate program faculty must be trained in culturally sensitive advising in order to make significant change. This could, they argued, lead to “disrupting processes that have historically perpetuated inequality in education experiences” (p. 54).…”
Section: Recruitment Questions Results and Implicationsmentioning
confidence: 99%
“…Educators in higher education must begin to listen to and learn from Latinx and other racially minoritized students to better understand how we can organizationally structure support systems and resources to set up these scholars for holistic success (Luedke et al, 2019). In a survey of 4,000 graduate students conducted by Golde and Dore (2001), most respondents indicated that after obtaining their terminal degrees, they aspired to be in teaching careers but felt inadequately prepared in their doctoral preparatory programs.…”
Section: Discussionmentioning
confidence: 99%
“…Many scholars have investigated peer and faculty mentoring of undergraduate STEM majors; however, most of these studies focus on the benefits to the mentees. For example, researchers have addressed the effect of being a mentor on student retention (Chelberg & Bosman, 2019;Damkaci, Braun, & Gublo, 2017;Lisberg & Woods, 2018;Wilson et al, 2012), STEM efficacy (Estrada et al, 2018;Lewis et al, 2018), academic and career motivation (Griffin, Pérez, Holmes, & Mayo, 2010), STEM content knowledge (Nelson et al, 2017), goal setting and career planning (Chelberg & Bosman, 2019;Mondisa, 2015;Nelson et al, 2017), and cultural capital (Hernandez et al, 2018;Luedke, McCoy, Winkle-Wagner, & Lee-Johnson, 2019). Consistent with Crisp and Cruz (2009) mentoring model for marginalized students, these research findings reinforce the need for a multifaceted approach to mentoring, which includes both the acquisition of STEM knowledge and skills as well as social support and guidance as students become integrated into the field.…”
Section: University-and School-based Stem Mentoringmentioning
confidence: 99%